A Syntactic Analysis Of The Basic Sentence Patterns In Ile Ape Dialect Of Lamaholot Language - Elizabeth Rilyn Marsella Marolly; Sebastianus Fernandez; Yosep B. Kroon; Zantty O. Padahana (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research examines how many basic sentence patterns there are in Ile Ape Dialect of Lamaholot Language, and what are the basic sentence patterns in Ile Ape Dialect of Lamaholot Language. The writer employed descriptive qualitative method to analyze and describe the data in this research. The data source of this research is the native speakers of Lamaholot Language, especially for Ile Ape Dialect. In this research, the writer used two research instruments to support the process of data collection they are, interview guidelines and recording device (smartphone). The data collection techniques applied in this research consist of three (3) techniques, including audio-recording, written documents collection, and elicitation. In order to analyze the data collected, the writer used technique of transcription, sentence translation, sentence selection, sentence analysis, and data description. The result of this research shows that, there are five (5) basic sentence patterns in Ile Ape Dialect of Lamaholot Language, they are: Pattern I: Subject + Verb (S + V); Pattern II: Subject + Verb + Object (S + V + O); Pattern III: Subject + Verb + Direct Object + Indirect Object (S + V + IO + DO); Pattern IV: Subject + Verb + Object + Object Complement (S + V + O + OC); and Pattern V: Subject + Subject Complement (S + SC).